Psychosomatics: Exploring the Role of the Mind-Body Connection in Causing Physical Illnesses - Jainish, Patel; Prittesh, Patel; Heer, Vaghela (Journal of Psychophysiology Practice and Research, 2022)
An overview of psychosomatic medicine explores how mind–body interactions contribute to physical illness. It reviews mechanisms, assessment approaches, and implications for integrated care.
Keywords: Psychosomatic; Mind-body; Chronic illnesses; Chronic Diseases